(untitled) (Research, Society and Development, 2020)
This study set out to isolate microrganisms strains with probiotic characteristics after simulating the in vitro digestion of sheep milk fermented by kefir grains. Three lactobacilli with probiotic characteristics were isolated and identified as Lactobacillus rhamnosus. Assays characterized these strains as probiotic since they tolerated acid pH and bile salts, had antibiotic resistance, antagonist activity, antioxidant activity, presence of β-galactosidase enzyme and other tests revealed adhesion capacity. All strains presented antioxidant activity and survived at different pH and bile salts. These strains can be considered safe because they were susceptible to antibiotics tested, possess antagonist activity to pathogens and high β-galactosidase activity. As to adhesion criteria (hydrophobicity and autoaggregation), L. rhamnosus Lb16 stood out, as it also adheres to the intestinal epithelium cells of mice. The analysis of L. rhamnosus Lb16 can assist the dairy industry to enhance the potential human health benefits of its products. This paper is an important contribution to probiotics isolated after simulation of the in vitro digestion of fermented sheep milk by kefir grains, this has a differential due to its different characteristics which afforded the isolation of resistant strains to gastrointestinal conditions.